Identification of diving athletes' sports specialization through their physical and functional attributes - Konopleva E. N.; Redi E. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the physical and functional attributes of athletes who excel in sailing, sprinting, and underwater sports.